India : Policy of Notes on Power - World Bank (Washington, DC, 2014)
The Clean Energy Ministerial (CEM) is a high-level global forum to promote policies and programs that advance clean energy technology, to share lessons learned and best practices, and to encourage the transition to a global clean energy economy. At the United Nations Framework Convention on Climate Change conference of parties in Copenhagen in December 2009, U.S. Secretary of Energy Steven Chu announced that he would host the first Clean Energy Ministerial to bring together ministers with responsibility for clean energy technologies from the world s major economies and ministers from a select number of smaller countries that are leading in various areas of clean energy. Currently, the 23 governments participating in CEM initiatives are Australia, Brazil, Canada, China, Denmark, the European Commission, Finland, France, Germany, India, Indonesia, Italy, Japan, Korea, Mexico, Norway, Russia, South Africa, Spain, Sweden, the United Arab Emirates, the United Kingdom, and the United States, and collectively account for 80 percent of global greenhouse gas emissions and 90 percent of global clean energy investment.